Respuesta :

[tex]\left(-\dfrac{1}{2}\right)(4x)(-2)(7y)(-1)\\\\=\left(-\dfrac{1}{2}\right)(-2)(4)(7)(-1)(x)(y)\\\\=(1)(4)(7)(-1)(xy)\\\\=(28)(-1)(xy)\\\\=(-28)(xy)\\\\=\boxed{-28xy}\to\boxed{\boxed{A}} [/tex]
AL2006

Your attachment says:            (-1/2) · (4x) · (-2) · (7y) · (-1)

Let's put together the
1st, 3rd, and 5th factors:        (-1/2) · (-2) · (-1)  =  -1

So now we have                      (-1) · (4x) · (7y)

Well                                           (4x) · (7y)  =  (4 · 7) · (x · y)  =  28 · x · y

So all together we have          (-1) · (28 · x · y)  =  -28xy  


ACCESS MORE